Effect of Upper Body Strength Training in Spatiotemporal Parameters of Gait In Individual with Thoracic Kyphosis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The human spine is an integral part of the human body. Its function includes mobilizing the torso, controlling postural stability, transferring, loads from upper body to lower body, all of which is essential for the activity of daily living. Spine deformity affects spinal mobility and trunk balance, thus altering locomotion pattern during each step. Spinal deformity also alters the center of body mass (com) during gait which leads to gait abnormality. Exaggerated thoracic kyphosis is common in the elderly as there is age related increase in thoracic spine curvature. Generally, patients with thoracic kyphosis mostly have gait impairment with reduced movement in upper limb strength and muscle mass gets altered in upper limb. Objective: The objective of the study is to study the effect of upper body strength training on spatiotemporal parameters of gait in individuals with thoracic kyphosis and to find out the effect of upper body strength program on gait parameters after thoracic kyphosis. Material and Method: In this interventional study a total of 25 individuals with in the age group of 20 to 50 years, were selected. Pre-test and post-test assessment was done using the outcome measures of flexi curve ruler to assess kyphosis index and spatiotemporal measurement. Exercises were administered for 6 weeks. Later, post-test assessment and statistical analysis was done to determine its significance. Results: According to the result, there was a considerable change in the stride length(p-value<0.0001) step length(p-value<0.0001) and cadence (p-value<0.0001). There was also a marked change in the kyphosis index. (p-value<0.0001). Conclusion: As per the result of this study, we conclude that the effect of upper body strength training on spatiotemporal parameters of gait in individuals with thoracic kyphosis was extremely significant.